PSYCHOLOGICAL BASIS OF THE PROBLEM OF INTEGRATION OF NATIONAL AND UNIVERSAL VALUES IN YOUTH - Kudratova Lola Ravshanovna (Journal of Applied Science and Social Science, 2026)
This article examines certain changes in young people’s attitudes toward national values under the influence of the modern information space, the internet, and social networks. It also explores the issue of ensuring balance and harmonization between national and universal human values. Some aspects of this problem are analyzed from a psychological perspective. Relevant psychological literature and scientific research on the topic are reviewed.